2012
DOI: 10.1007/s00214-012-1221-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mutations on the absorption spectra of copper proteins: a QM/MM study

Abstract: The ground and excited state properties of copper proteins are studied and analyzed using hybrid quantum mechanics/molecular mechanics technique. Wildtype plastocyanin, characterized by an intense blue color, and wild-type nitrosocyanin, a red protein, are considered. These proteins differ from some ligands of the copper containing chromophore; we also studied the effects of selective mutations of one of the active site residue in plastocyanin. It is shown that this mutation is able to strongly modify the UV/V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Our results are not directly comparable with those obtained experimentally for the full protein because we neglect to account for the copper center, which is responsible for a very bright red absorption. However, previous computational studies have shown how time‐dependent (TD) DFT is able to provide a good representation of such transitions . An analysis of the convergence of the simulated absorption spectrum with the number of snapshots is presented in Figure S1 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are not directly comparable with those obtained experimentally for the full protein because we neglect to account for the copper center, which is responsible for a very bright red absorption. However, previous computational studies have shown how time‐dependent (TD) DFT is able to provide a good representation of such transitions . An analysis of the convergence of the simulated absorption spectrum with the number of snapshots is presented in Figure S1 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…The QM-MM absorption spectrum obtained at TDDFT level putting only the copper ion and the ligating aminoacids in the QM part is also reported in Fig. 1.3 and one can notice the very good agreement with the experimental values, providing that the PE effect is taken into account, on the contrary ME gives totally unreliable results indicating an important effects of electrostatic and polarization effects [57]. Note also that more in detail the PE spectrum is composed of a large tail in the near infrared region while the visible part is constituted by the huge absorption band peaking at 600 nm and of a much less intense band appearing close to 490 nm.…”
Section: Absorption Of Copper Proteins (From Red To Blue Protein)mentioning
confidence: 54%
“…1.3) are metallo-protein present in superior plants were they assure electron-transfer during the photosynthetic process [57,58]. The active site of the protein is constituted by a copper ion complexed by four aminoacids residues: one deprotonated cysteine, one methionine and two hystidines.…”
Section: Absorption Of Copper Proteins (From Red To Blue Protein)mentioning
confidence: 99%
See 2 more Smart Citations